Mobile Microcredit Uptake and Performance of Small and Micro Enterprises: Case Study, Mukono Town - Judith Kisaakye (Uganda Christian University, 2024)
The use of mobile phones is embraced at an incredible rate, and this study aimed to determine the mobile microcredit uptake and performance of SMEs in Mukono. SMEs encounter difficulties in surviving and growing due to limited funds. The study was based on the following research objectives: To examine the effect of mobile cost of credit on the performance of SMEs, to examine the effect of mobile credit perceived risk on the performance of SMEs, and to establish the influence of mobile credit accessibility and Eligibility on the performance of SMEs in Mukono, The study employed an explanatory research design. The 65 SMEs that operated in Mukono made up the study population. A sample size of 57responders was employed. Questionnaires were used to gather data. The pilot study was conducted by the researcher prior to the actual data collection. To ensure validity and reliability, the information on the data collection instruments was carefully examined. The Cronbach Alpha coefficient was used to guarantee reliability. The study employed descriptive statistics, such as percentages and frequencies, to analyze the data, which were then presented in tables and figures. The first objective's findings demonstrated that the cost of credit for mobile loans had a significant positive impact on SMEs' performance (r =0.475, p =0.01) and a moderate correlation suggesting that the decrease on mobile cost of credit trend to increase business turn over. The second objective's findings(r = 0.04, p =0.240) indicated that the perceived risk associated with microcredit offered by mobile loans encouraged SMEs to obtain them, thus improving performance, however the relationship was not particularly strong. And the third objective's findings indicated that the performance of SMEs was positively impacted by the accessibility (r =0.275, p =0.113) and eligibility (r= 0.204, p =0.240) of mobile loans. In particular, the study found that the respondents preferred mobile loans for the following reasons: the amount charged for application fees, the amount charged for processing fees, and the interest rates on mobile loans, among other reasons. It also found that the respondents preferred mobile loans because they were concerned about the risk of not being able to repay a financial institution loan on time. Other factors that led the respondents to choose mobile loans include the length of time it took for a loan from another financial institution to be processed, the accessibility of mobile loan applications, and the flexibility of loan applications.